Integration of Scientific Literacy and Islamic Law in the Practice of in Vitro Fertilization (IVF) - Ajrun 'Azhim Al As'hal; Ahmad Fauzi (USRATY : Journal of Islamic Family Law, 2025)
The integration of scientific literacy and Islamic law in the practice of In Vitro Fertilization (IVF) represents a complex convergence between biomedical innovation and religious ethical norms. This study investigates how IVF procedures—widely practiced in modern medicine—can be understood, ethically evaluated, and religiously regulated through the lived experiences of Muslim patients and key stakeholders. The core issue explored is the tension between medical needs for reproductive technologies and Islamic legal concerns over lineage, marital legitimacy, and the prohibition of third-party donors. This research offers a novel approach by combining scientific literacy and Islamic jurisprudence within an empirical context. Adopting a qualitative field research design, the study was conducted in two major Indonesian cities and involved Muslim IVF patients, fertility specialists, and local Islamic scholars as key informants. Data were collected through in-depth interviews, observation, and analysis of relevant documents, including fatwas and clinical guidelines. The findings reveal that scientific understanding plays a vital role in shaping patients’ ethical decisions, while Islamic legal principles remain central in defining moral boundaries. This integrative perspective reframes IVF as a potentially permissible medical practice, provided it adheres to foundational Islamic norms. The study concludes that a field-based integrative approach offers a balanced ethical framework that respects both biomedical responsibility and religious observance.